Durability Improvement Strategies for Concrete Structures of Comprehensive Transport Infrastructure - Huajian Li; Chengxian Ma; Zhiqiang Yang; Haoliang Dong; Zhonglai Yi (中国工程科学)
Transport infrastructures, including railways, highways, waterways, and civil aviation systems, rely heavily on reinforced concrete as their primary structural material. Ensuring the durability of concrete structures is critical for maintaining transport safety, improving transportation efficiency, and extending service life. This study investigates the service status of transport infrastructure concrete structures and identifies key durability issues and challenges related to design theories, construction technologies, and operational systems. Advanced monitoring technologies for surface microcracks, ion permeation, internal damage, and reinforcement corrosion are reviewed, alongside precise maintenance technologies for concrete structures. Based on these findings, recommendations for enhancing the durability of these concrete structures are proposed, emphasizing the need for comprehensive top-level design, technological innovation, and the establishment of standards systems. These measures aim to ensure the long-term safety and reliability of the transport infrastructure concrete structures.